Effect of Technetium-99 Conjugated with Methylene Diphosphonate on IgM-RF, IgG-RF and IgA-RF - 黄安斌 余立凯 沈凌汛 (Current medical science, 2003)
To explore the effect of technetium-99 conjugated with methylene diphosphonate (^99Tc-MDP) on IgM-RF, IgC--RF and IgA-RF (RFs), 47 cases were selected for study, including 33 patients with rheumatoid arthritis (RA) and 15 patients with joint pain/arthritis. After ^99Tc-MDP for drips model being given to the patients by intravenous drip 0.2 g daily for 5 days, the injection A and B models of ^99Tc-MDP were used to the patients by intravenous injection one set daily for 10days, that was one course of treatment. The next course started after 10 days. Each case used it from 2 to 4 courses of treatment. The RFs in serum were determined by the method of enzyme-linked immunoabsorption assay (ELISA) before and after 2 and 4 courses of treatment. In the patients with RA, the concentrations of IgM-RF were 296.2±108.4 IU/ml, 189.5±92.3 IU/ml and107.8±72.5 IU/ml; the concentrations of IgG-RF were 325.6±126.2 IU/ml, 209.7±98.2 IU/ml and 160.2±80.8 IU/ml; the concentrations of IgA-RF were 330. 4±136.3 IU/ml, 210. 7±89.2 IU/ml and 148.8±72.2 IU/ml before and after 2 and 4 courses of treatment, respectively. The concentrations of the above RFs were significantly lower after 2 and 4 courses than those before treatment (P<0.05 and P<0.01). There was no significant difference in RFs concentrations in the patients with joint pain/arthritis before and after use of ^99Tc-MDP. In the patients with positive RFs before treatment, the RFs concentrations were decreased significantly after 2 and 4 courses of treatment (P<0.05 and P<0.01). There was no obvious change of RFs concentrations in the patients with negative RFs after treatment of ^99Tc-MDP. It was concluded that ^99Tc-MDP could obviously reduce the abnormally high concentrations of RFs, but not influence the normal RFs, which indicated that ^99Tc-MDP has an important effect on controlling the activities of RA.